Skills and skilled work : an economic and social analysis - Green, Francis [Verfasser] (Oxford University Press, 2013)
"Skills are frequently in the news and in the public eye in every country. Stories highlight concerns about education and literacy standards, grades, learning by rote, and university students being unprepared for work, as well as debates surrounding internships and apprenticeships, and social exclusion through skills policy. The recent financial crisis has forced education and training to take a back seat, and has caused an increase in youth unemployment. Skill and skilled work are widely considered important for promoting both prosperity and social justice. But how do we define skill? 'Skills and Skilled Work' brings together multiple perspectives - economics, sociology, management, psychology, and political science - to present an original framework for understanding skills, skilled work, and surrounding policies. Focussing on common themes across countries, it establishes the concept and measurement of skill, and investigates the role of employers, workers, and other social actors. It considers a variety of skill problems and how a social response from the government can be understood. Based on the findings of economics, management science, and theories of social determination, it develops a rationale for social intervention beyond market failure." (Verlag, BIBB-Doku)

Table of contents: PART I : SKILL CONCEPTS AND FRAMEWORK 1: Skilled Work and Job Quality 2: What Is Skill? 3: Framing the Analysis of Skilled Work 4: The Measurement of Skill PART II: THE PLAYERS 5: Employers and the Evolution of Skilled Work 6: Employers and Skill Formation 7: Skills and Skilled Work for Workers PART III : SYSTEMS AND INTERVENTIONS 8: Skill Matching Processes, Problems, and Outcomes 9: Skill Systems and the Role of the State 10: Skills Analysis for Modern Economies 11: Threads and Limits
Keywords: G 1.2.3 Qualifikationsentwicklungen; L 6.3.1 Diagnose- & Messinstrumente; G 1.2.3.2 Anforderungen & Bedarfe; G 1.2 Arbeitsmarkt; Kompetenz; Qualifikation; Begriff; Kompetenzfeststellung; Qualifikationsanforderung; Mittlere Qualifikation; Arbeitskräftenachfrage; Mismatch; Qualifikationsbedarf; Früherkennung; Prognose